2000
DOI: 10.1093/oxfordjournals.bja.a013434
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echocardiographic assessment of haemodynamic changes during laparoscopic herniorrhaphy in small children

Abstract: Laparoscopic techniques for surgery are gradually becoming established in paediatric surgery. Technical aspects, such as the maximum safe gas insufflation pressure, are still open to discussion. We used transoesophageal echocardiography to study the haemodynamic changes in eight small children undergoing laparoscopic herniorrhaphy, with two different levels of intra-abdominal pressure (IAP), 6 and 12 mm Hg. End-tidal carbon dioxide tension was maintained constant at 4.3-4.7 kPa. After baseline measurements, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Rarely, invasive monitoring, such as the placement of an indwelling arterial catheter or a transesophageal color-Doppler probe, has been used to better evaluate cardio-respiratory changes in restricted series of highrisk patients [3,7,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, invasive monitoring, such as the placement of an indwelling arterial catheter or a transesophageal color-Doppler probe, has been used to better evaluate cardio-respiratory changes in restricted series of highrisk patients [3,7,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the increase in abdominal pressure and Paco 2 from the carbon dioxide insufflation leads to an increase in peripheral vascular resistance and a decrease in cardiac index (CI) [4]. Sakka et al [1] used transesophageal echocardiography to demonstrate a 13% decrease in CI at 12 mm Hg intraabdominal pressure in healthy children aged 2 to 6 years. However, the CI returned to baseline with reduction of the intraabdominal pressure to 6 mm Hg, and neither pressure appeared to lead to clinically important changes in this patient population [1].…”
Section: Discussionmentioning
confidence: 99%
“…Sakka et al [1] used transesophageal echocardiography to demonstrate a 13% decrease in CI at 12 mm Hg intraabdominal pressure in healthy children aged 2 to 6 years. However, the CI returned to baseline with reduction of the intraabdominal pressure to 6 mm Hg, and neither pressure appeared to lead to clinically important changes in this patient population [1]. In addition, Gueugniaud et al [2] reported a 67% decrease in aortic blood flow indexed to body surface area and 162% increase in systemic vascular resistance indexed to body surface area compared with control values in a series of 12 ASA class 1 male patients aged 6 to 30 months with 10 mm Hg intraabdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, many of these infants will have difficulties with failure to thrive or gastroesophageal reflux, requiring placement of a gastrostomy tube with or without a fundoplication. These procedures have been routinely performed laparoscopically in most children without cardiac disease with decreased infection and complication rates, as well as shorter hospital stays compared with the equivalent open procedures [1]. Patients with known congenital heart defects would certainly benefit from these aspects of laparoscopic surgery, but historically, these children were not commonly offered minimally invasive options because of the perceived cardiovascular risks associated with laparoscopy.…”
mentioning
confidence: 99%